Students’ Perspective on Project-Based Assessment in Writing Classroom - Amalul Umam; Tiwi Handini (Journal of English Education and Teaching, 2021)
This study aimed to examine students' perspectives at the university level regarding project-based assessment in writing classes. This research is conduct at one of the universities in Bogor city. Participants in the study numbered eight female students, of whom they had written an academic article before. The method in this study uses qualitative, which uses interviews and documentation in its data collection. The final result obtained is that some students' opinions on project-based assessment include not easy to do, add experience in terms of writing, and take a long time. Benefits of project-based assessment include writing, honing writing skills, and being selective in choosing information—problems faced by students such as lack of time, looking for reference material, and lazy taste.